FORMULASI KEBIJAKAN PERATURAN DESA DI DESA BATAKA KECAMATAN IBU SELATAN KABUPATEN HALMAHERA BARAT - META, KARLIVON; LALOMA, ALDEN; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2018)
This Research Aims To Explain Regarding Village Rule Policy Formulation in Bataka Village. AndDescribe Formulation of Village Rule Policy, This Research Using Descriptive Method of QualitativeApproach, and technique of data collecting by observation, interviewing technique and documentationResult of Research is Process Formulation of Village Rule Policy which done through four Phase NamelyStage of Problem Formulation, Stage of Policy Agenda , Alternative Stages of Policy Stages of PolicyDetermination, Based on Research Results and Field Findings, Concerning Formulation of Village RulePolicy In Bataka Village is a Formulation Process of Village Rural Policy in Bataka Village Seen At ThisStage The Government Performs only Temporary APBDesses Other Issues Urges such as village cleanlinessand village village security do not. At the stage of the policy agenda of the preparation of APBDesa hasbeen running, it is seen in the process that goes both internal government and BPD sementra it for otherproblems outside the APBDES not well done, At the alternative stage of supporting facilities for APBDESalternative selection is not available well this resulted in the process the formulation of village regulationsfocused only on APBDES, several matters related to the process of formulation of village regulation policy,among others: Need adannya done in the identification problem about cleanliness and security to enter inAgenda of Policy, village government problem in bataka village need to accomodation in village regulations.Keywords: Formulation, Policy, Village Regulation.